Macroeconomic Analysis and Policy : The Case of Egypt - Hussein, Shehadah (International Monetary Fund, 1997)
This book aims at illustrating the process of formulating a hypothetical macroeconomic and structural adjustment program, which is a central element in the financial programming courses offered in the IMF Institute. The series of workshops contained in the book elaborate on key concepts for the four main macroeconomic sectors, real, fiscal, monetary, and external sectors-and on forecasting techniques using Egypt as a case study.